2011
DOI: 10.1111/j.1365-263x.2011.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of smear layer removal on primary tooth pulpectomy outcome: a 24‐month, double‐blind, randomized, and controlled clinical trial evaluation

Abstract: The pulpectomy outcome was improved by smear layer removal. The outcome for teeth with pulpal necrosis, pre-operatory symptoms, or periapical/inter-radicular radiolucency was significantly improved by removal of the smear layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 22 publications
(65 reference statements)
3
65
1
9
Order By: Relevance
“…Similarly, clinical research found that smear layer removal from symptomatic teeth with pulp necrosis is associated with a higher success rate for endodontic therapy (3). From these perspectives, the primary tooth pulpectomy protocol taught and practiced at UFRGS contemplates the use of an intra-canal dressing (calcium hydroxide) between sessions and smear layer removal using 17% EDTA in cases of fistula, swelling, suppuration and pulp necrosis, with or without furcation/periapical involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, clinical research found that smear layer removal from symptomatic teeth with pulp necrosis is associated with a higher success rate for endodontic therapy (3). From these perspectives, the primary tooth pulpectomy protocol taught and practiced at UFRGS contemplates the use of an intra-canal dressing (calcium hydroxide) between sessions and smear layer removal using 17% EDTA in cases of fistula, swelling, suppuration and pulp necrosis, with or without furcation/periapical involvement.…”
Section: Discussionmentioning
confidence: 99%
“…First, preoperative radiographs were obtained and the length of the working area was set at 1-2 mm short of the radiographic apex (3,8,9). Treatment was performed in a single visit for vital and non-infected teeth and a minimum of two appointments for teeth with abscesses, swellings or periapical and/or inter-radicular radiopacities .…”
Section: Clinical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Barcelos et al (2012) showed increased success from 70% to 91% when the smear layer was removed from primary teeth during a pulpectomy. The study used a citric acid solution to remove the smear layer, performed treatment over two visits, used a camphorated paramonochlorophenol interim intracanal medicament, irrigated with 2.5% NaOCI, obturated the primary canal with zinc oxide-eugenol paste, and evaluated the outcome after twenty four months.…”
Section: Lrrigant Usedmentioning
confidence: 99%
“…Although different protocols for pulpectomy in primary teeth have been described in the literature (Mortazavi & Mesbahi, 2004;Trairatvorakul & Chunlasikaiwan, 2008;Barcelos et al, 2012), they all agree that pulpectomy procedures are feasible only in teeth exhibiting minimal physiological or pathological root resorption, not exceeding 1/3 of the root length.…”
Section: Introductionmentioning
confidence: 99%